Consequences and determinants of IFRS convergence in India. Issue 2 (7th March 2020) - Tawiah, Vincent; Boolaky, Pran
Abstract : Purpose: The purpose of this paper is to provide evidence of how convergence to International Financial Reporting Standards (IFRS) impacts accounting values and the determinants of variation in equity adjustments among Indian companies. Design/methodology/approach: Using a sample of 323 listed companies, the authors empirically test whether there is a significant difference between converged IFRS (Ind.AS) and Indian Generally Accepted Accounting Principles (GAAP) (AS) reported figures and ratios and why companies adjust differently. Findings: This paper reveals that fair valuation under Ind.AS causes a significant decrease in goodwill. A substantial decrease in both current and long-term liabilities because of non-recognition of proposed dividend, discounting of long-term provision per Ind.AS was also found. The variations in equity adjustment were significantly influenced by capital structure, level of family control and auditor type. Practical implications: This paper provides insights to users who are interested in historical data, that Ind.AS brings significant changes in the accounting values and ratios and the impact differs among companies based on capital structure, ownership and auditor type. Originality/value: This paper contributes to the literature of IFRS convergence in India by providing rational analysis of the differences between IFRS, Indian converged GAAP and Indian local GAAP among companies and its impact on accounting values.